Indonesia's Humanitarian Diplomacy in the Midst of Gaza and Ukraine Crises: Narratives, Challenges, and Soft Power Potentials - Sholahuddin Al-Fatih (Politeknik Siber Cerdika Internasional, 2025)
The global humanitarian crises in Gaza and Ukraine have become a test for the diplomatic position of developing countries in the international system. Indonesia, as a country with a strong identity in international solidarity and the principle of free and active foreign policy, plays an interesting role in navigating humanitarian diplomacy. Indonesia's involvement in the Gaza issue shows a commitment based on humanitarian solidarity, while its approach to Ukraine is more neutral and strategic. This context is important to analyze to see the potential of Indonesia's soft power as a moral actor at the global level. This study aims to evaluate the practice of Indonesia's humanitarian diplomacy in two contemporary conflict terrains-Gaza and Ukraine-by examining the narratives built, implementation challenges, and the extent to which it strengthens Indonesia's position in international diplomacy. The approach used is qualitative-descriptive with methods of diplomatic discourse analysis, document study, and observation of government statements, media, and relevant international cooperation. The results show that although Indonesia is consistent in promoting humanitarian and justice values, there are limitations in logistical capabilities, diplomatic access, and direct influence on conflict actors. However, the narratives built in humanitarian diplomacy have increased positive perceptions of Indonesia in the Global South, and opened strategic space in the utilization of soft power in the future, especially in the multilateral realm.